The effects of debate competition on critical thinking among Malaysian second language learners - Othman, Moomala; Sahamid, Husniah; Zulkifli, Muhammad Harith; Hashim, Rosnani; Mohamad, Faizah (IDOSI Publications, 2015)
Debate is a common co-curricular activity involving most Malaysian schools at the district level. Every year, each school would send three students to represent its team. In this study, forty (40) second language learners, aged 16 years old, were involved in a two hour debate activity carried out three days per week for three consecutive weeks. This activity was organized by their school seniors, aged 18 years, as part of their English assignment. A pre-post critical thinking test was carried out among the debaters and at the end of the activity, a survey was undertaken to gauge their perception of the thinking process they had experienced. The result revealed that there was a significant difference in their critical thinking skills before and after the debate activity as the intervention. The survey and teacher observation offered feedback on how debate foster their critical thinking. Among others, it showed the importance of scaffolding and collaborative learning in enhancing critical thinking. Another factor is the fact that debate involves argumentation, reasoning, explanation and questioning, all important critical thinking skills. Key words:Critical thinking Debate competition Second language learners Argumentation Explanation skill Reasoning skill Questioning skill Scaffolding collaborative thinking